Samiske barnehagers rolle i språkrevitaliseringa - Rasmussen, Torkel (Nordlyd, 2022)
More than a thousand children attend Sámi kindergartens daily, while quite a number of Sámi children get Sámi language instruction in other kindergartens. This activity is one of the most important arenas for transmission and acquisition of Sámi languages. A question raised in this article is how these kindergartens are used as research fields in the disciplines of language and sociology and early childhood pedagogy. Another question is what kind of language teaching models are used. The article shows that little research has been carried out on how Sámi kindergartens teach Sámi language. There is also little research done on the results from this education. A review of the Sámi kindergartens’ history shows that statistical material on Sámi kindergartens and Sámi language instruction in other kindergartens is available only from some geographical areas, and existing statistical information is only partly suitable for analysis. This makes it difficult to use existing material to monitor the vitality of Sámi languages. The article calls for more research on Sámi kindergartens and language teaching models used in them. A goal could be to create a basis for monitoring this crucial indicator of language vitality for Sámi languages: whether new generations of Sámi become Sámi-speakers or not. This should be followed up with more research on the language teaching models used in Sámi kindergartens I de samiske barnehagene har mer enn tusen barn sitt daglige virke, mens en god del andre samiske barn får opplæring i samisk i andre barnehager. Denne virksomheten er uten tvil en av de viktigste arenaene for overføring av og opplæring i samiske språk. Men hvordan har disse barnehagene blitt benyttet som forskningsfelt av forskere inne disiplinene språksosiologi og småbarnspedagogikk? Bruker disse barnehagene sterke eller svake språkopplæringsmodeller for samisk språk? Artikkelen viser både at det er forsket lite på hvordan de samiske barnehagene jobber med samisk språk, og svært lite på utkomme av denne opplæringa. En ...